Waste at Wedding Party (Social Reality Study of Walimatul 'Ursy in Gampong Meunasah Baro, Seulimeum District, Aceh Besar Regency) - Salahuddin; Muhammad Hasan (Budapest International Research and Critics University, 2021)
Marriage is part of the teachings of the Islamic religion that must be obeyed and carried out by everyone if they already have the ability to be physically and mentally. Marriage is considered imperfect by some people in Gampong Meunasah Baro, Seulimeum District, Aceh Besar Regency if the implementation is not accompanied by a celebration, even though the marriage is legal according to Islamic law. Therefore, after marriage, walimah wil be carried out, which is a celebration that accompanies the marriage to make it official so that it is known in general by the public. The implementation of walimatul 'ursy in Islam is more emphasized on simplicity, convenience, happiness and pleasure or cheapness according to needs, not based on desire. The purpose of this research is to describe redundant in a wedding reception, as well as to describe the impact of waste on the party. In this study, the researchers used qualitative method. The results of the study related to the wedding party in Gampong Meunasah Baro, Seulimeum District, Aceh Besar Regency showed that the celebration of the wedding party was already a tradition that was carried out after the wedding. This tradition is carried out to honor guests, but in the implementation of the reception based on Islamic law, it is detected that there is a redundancy that is often carried out both by the wedding party organizer and by the invited guests. The results of the study show that the waste carried out by the host as the implementation of the intent of the wedding party in the form of providing too much food so that it cannot be finished. After the wedding, a lot of food is wasted. Meanwhile, the waste done by the invited guests either intentionally or unintentionally by not finishing the food or leaving a lot of food that has been placed on the plate. However, in the view of customary law, this is considered normal, even though they know that redundant is a friend of the devil. The results of the study also show that the wedding party has had a good cultural impact, but has no impact on social, religious or economic terms.